STRUKTUR KALIMAT BAHASA ARAB DAN BAHASA PERSIA - Fatimah, Siti; Budianto, M. Agus (-)
This paper describes the differences between Arabic and Persian sentence structure to help beginner Persian learners, especially those with Arabic language knowledge. This is a library research using linguistic approach and contrastive analysis to compare both sentence structre to predict difficulties that might appear in learning Persian. The differences of both languages, i.e. : 1) there ara two formulas of Arabic sentence structure: a) subject + predicate, and b) predicate + subject or predicate + subject + object. While in Persian the formula is subject + predicate or subject + object + predicate; 2) negative sentences of both languages use negative particle, but Arabic has various ones and most of them change the iâ€™rab; 3) Arabic passive sentences follows the wazn ÙÙØ¹ÙÙ„ÙŽ (past) and ÙŠÙÙÙ’Ø¹ÙŽÙ„Ù (present), while in Persian uses ending of Ø´Ø¯Ù† after the past verbs; 4) Arabic imperatives are formed by adding hamzah wasal replacing the huruf mudaraâ€™ah, while in Persian by adding Ø¨Ù€Ù€ before the root of present verbs; 5) fiâ€™l nahyi in Arabic are formed by adding lam an-nahiyah before majzum present verbs, while in Persian by adding Ù†Ù€Ù€ before root of present verbs.